ESP Students Processing Multimodal Websites Through the Eye-tracking Technique - Bort Mir, Lorena; Fortanet Gómez, Inmaculada (International Journal of English Studies, 2024)
With the increasing importance of the Internet for teaching and learning, websites have become an interesting pedagogic resource as they entail interconnected modes of communication to convey meaning. When combined with multimodal website analysis, eye-tracking can provide valuable insights into how users engage with different modes of communication on a website. In this pilot experimental study, we analyze and compare how twenty-six Computer Science and Business and Law double degree students process two entrepreneurial websites to understand their meaning through eye-tracking (RealEyeTM online tool, https://www.realeye.io/). On the one hand, we analyze to what extent the eye-tracking technique contributes to the ESP students’ perception of the multimodality of websites. On the other hand, we tested the students’ reactions to using an activity with an eye-tracker in ESP courses, and we compared the results between two academic backgrounds. Our results show more fixations on titles and body text than photos or graphics, and the overall reading pattern entails fast scanning with no significant differences between the two groups. This research proves that eye-tracking can be a valuable tool for understanding how people process multimodal texts. It can be used to improve the effectiveness of such texts for communication and learning.